Progression of cervical dilatation in normal human labor is unpredictable. (3rd September 2015) - Ferrazzi, Enrico; Milani, Silvano; Cirillo, Federico; Livio, Stefania; Piola, Cinzia; Brusati, Valentina; Paganelli, Andrea
Abstract: Introduction: The aim of this study was to analyze how the progression of cervical dilatation in active labor can be predicted by digital assessment in low‐risk pregnant women, in spontaneous labor at term. Material and methods: This prospective observational study was performed on 328 women with singleton term gestations experiencing midwife‐led labor according to local protocols, progressing to full dilatation and spontaneous delivery without any medical intervention. Mixed nonlinear models were adopted to (i) model individual cervical data into centile curves and (ii) calculate the time needed to gain 1 cm in cervical dilatation (TNG1cm ) modeled as a function of current dilatation. We correlated the first and the last TNG1cm on parturients with at least four cervical data points. Results: TNG1cm showed large variations, both before and after 6 cm. This variability of natural progression of cervical curves described by the 10th and 90th centiles exceeded the differences observed in published curves from cohorts homogeneous for parity, weight and ethnicity. There was no significant correlation between the first and the last TNG1cm . Neonatal base excess was not significantly different in women with TNG1cm <10th centile and >90th centile. Conclusions: The rate of cervical dilatation, traced by parsimonious nonlinear mixed models, is largely unpredictable in the case of spontaneous naturally progressing labor, even when possible larger individual variability is excluded by prudent clinical rules. Future research in labor and delivery should be focused on the diagnosis of the causes that lie behind apparently erratic cervical changes.